The macrophage scavenger receptor A is host-protective in experimental meningococcal septicaemia. - Plüddemann, A; Hoe, J; Makepeace, K; Moxon, E; Gordon, S (Public Library of Science, 2009)
Macrophage Scavenger Receptor A (SR-A) is a major non-opsonic receptor for Neisseria meningitidis on mononuclear phagocytes in vitro, and the surface proteins NMB0278, NMB0667, and NMB1220 have been identified as ligands for SR-A. In this study we ascertain the in vivo role of SR-A in the recognition of N. meningitidis MC58 (serogroup B) in a murine model of meningococcal septicaemia. We infected wild-type and SR-A(-/-) animals intraperitoneally with N. meningitidis MC58 and monitored their health over a period of 50 hours. We also determined the levels of bacteraemia in the blood and spleen, and measured levels of the pro-inflammatory cytokine interleukin-6 (IL-6). The health of SR-A(-/-) animals deteriorated more rapidly, and they showed a 33% reduction in survival compared to wild-type animals. SR-A(-/-) animals consistently exhibited higher levels of bacteraemia and increased levels of IL-6, compared to wild-type animals. Subsequently, we constructed a bacterial mutant (MC58-278-1220) lacking two of the SR-A ligands, NMB0278 and NMB1220. Mutation of NMB0667 proved to be lethal. When mice were infected with the mutant bacteria MC58-278-1220, no significant differences could be observed in the health, survival, bacteraemia, and cytokine production between wild-type and SR-A(-/-) animals. Overall, mutant bacteria appeared to cause less severe symptoms of septicaemia, and a competitive index assay showed that higher levels of wild-type bacteria were recovered when animals were infected with a 1ratio1 ratio of wild-type MC58 and mutant MC58-278-1220 bacteria. These data represent the first report of the protective role of SR-A, a macrophage-restricted, non-opsonic receptor, in meningococcal septicaemia in vivo, and the importance of the recognition of bacterial protein ligands, rather than lipopolysaccharide.